The marketing agency blueprint the handbook for building hybrid PR, SEO, content, advertising, and Web firms - Roetzer, Paul, 1978-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2012)
"Build a disruptive marketing agency for the modern ageThe marketing services industry is on the cusp of a truly transformational period. The old guard, rooted in tradition and resistant to change, will fall and new leaders will emerge. Hybrid marketing agencies that are more nimble, tech savvy, and collaborative will redefine the industry. Digital services will be engrained into the DNA and blended with traditional methods for integrated campaigns. The depth, versatility, and drive of their talent will be the cornerstones of organizations that pursue a higher purpose. The Marketing Agency Blueprint is a practical and candid guide that presents ten rules for building such a hybrid agency.The new marketing agency model will create and nurture diverse recurring revenue streams through a mix of services, consulting, training, education, publishing, and software sales. It will use efficiency and productivity, not billable hours, as the essential drivers of profitability. Its value and success will be measured by outcomes, not outputs. Its strength and stability will depend on a willingness to be in a perpetual state of change, and an ability to execute and adapt faster than competitors. The Marketing Agency Blueprint demonstrates how to: Generate more qualified leads, win clients with set pricing and service packages, and secure more long-term retainers Develop highly efficient management systems and more effective account teams Deliver greater results and value to clients This is the future of the marketing services industry. A future defined and led by underdogs and innovators. You have the opportunity to be at the forefront of the transformation"--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Marketing; Electronic books